The Analysis of Surgery Patients Anxiety Reviewed from Pre Operative Services at Dr. R. M Djoelham Binjai Public Hospital - Juliandi Harahap; Chairul Syah Putra; Rivan Wiriadibrata (Journal La Medihealtico, 2021)
Surgery is a form of therapy that can threaten the integrity of a person's body and soul. The psychological response that usually occurs in preoperative patients is anxiety. Anxiety is an emotional reaction to subjective individual judgment, which is influenced by the subconscious and the cause is not specifically known. Type of research is quantitative and qualitative research (method mixed). This research was conducted at DR. R.M Djoelham general hospital Binjai. Qualitative population of surgeons, anesthetists and nurses at RSUD DR. RM Djoelham Binjai, samples obtained by Purposive Sampling as many as 33 people. Data were analyzed by univariate, bivariate (Chi Square), Multivariate (logistic regression). Based on these results it is concluded that there is a relationship between providing information, consultation and education on patient anxiety. Based on the results of the bivariate analysis, it is found that there is a relationship in the dimension of Information Giver has a value of p (sig) 0.037, consultation (sig) 0.005, education p (sig) 0,002. The concluded that there is a relationship between providing information, consultation and education on patient anxiety. Based on the results of interviews from informants, it was found that the provision of information, consultation and education before or after the operation had been implemented, both DPJP doctors, anesthetists and nursing staff.